ARTIFICIAL INTELLIGENCE AND BIG DATA - Shandilya, Shivangi; Sangwan, Surekha; Yadav, Ritu (IJRDO -Journal of Computer Science Engineering, 2015)
Artificial intelligence (AI) interests the study and development of intelligent machines and software. The related ICT research is highly technical and specialized, and its central problems include the development of software that can reason, gather knowledge, plan intelligently, learn, communicate, scent and Manipulate objects. It also allows users of big data to automate and enhance complex descriptive and predictive analytical tasks that, when performed by humans, would be extremely labor acute and time consuming. Thus, unleashing AI on big data can have a significant impact on the role data plays in deciding how we work, how we travel and how we can conduct business.